Kontribusi Arkeologi Dalam Penanganan Sengketa Tanah: Kasus Pada Masyarakat Pollung - Ketut Wiradnyana; Lucas Partanda Koestoro (Berkala Arkeologi Sangkhakala, 2015)
Archaeology, as a science, has to be able to provide welfare to the communities, which includes not only material things but also knowledge and explanation regarding problems among the communities in cultural context. In relation to a land dispute between the traditional community of Pollung and Toba Pulp Lestari Ltd. Co., regarding the Pollung’s village and traditional land, archaeology can be used to answer whether or not there were once settlement activities in the disputed piece of an area. The methods used in relation to the purpose are excavation, interviews, and library research (bibliographical research). The entire data was studied using inductive scheme of thought in descriptive qualitative format. The resulted archaeological data can prove that there were activities in the past as well as the period (date) when the activities were carried out, while anthropological data will support the knowledge about the functions and systems of land ownership among the Batak community at Pollung, Humbang Hasundutan, in North Sumatra.